2003
DOI: 10.1128/jvi.77.17.9723-9727.2003
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Intermediate-Stage Variants of Simian Immunodeficiency Virus Replicate Efficiently in Cells Lacking CCR5

Abstract: Primate lentiviruses are thought to use the chemokine receptor CCR5 as the major coreceptor for entry into cells. Here we show that some variants of simian immunodeficiency virus (SIV) replicate efficiently in peripheral blood mononuclear cells (PBMCs) lacking a functional CCR5. There were differences in the replication patterns of sequential variants that evolved during SIVMne infection; the late-stage pathogenic variants were unable to replicate in PBMCs lacking CCR5, whereas the early-and intermediate-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…recently showed that a mutated CCR5 gene encoding a truncated molecule that is not expressed on the cell surface does not protect sooty mangabeys from infection with the “R5-tropic” SIVsmm virus in vivo (Riddick et al, 2010). This, together with our data, support previous studies (Forte et al, 2003) suggesting that other surface molecules may also serve as co-receptors for SIV. SIV Env has been shown to mediate target cell entry in cell-to-cell fusion assays via interaction with chemokine receptor-like orphan receptors such as CXCR6 (STRL33/Bonzo) and GPR15 (BOB) (Edinger et al, 1998; Lauren et al, 2006; Pohlmann et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…recently showed that a mutated CCR5 gene encoding a truncated molecule that is not expressed on the cell surface does not protect sooty mangabeys from infection with the “R5-tropic” SIVsmm virus in vivo (Riddick et al, 2010). This, together with our data, support previous studies (Forte et al, 2003) suggesting that other surface molecules may also serve as co-receptors for SIV. SIV Env has been shown to mediate target cell entry in cell-to-cell fusion assays via interaction with chemokine receptor-like orphan receptors such as CXCR6 (STRL33/Bonzo) and GPR15 (BOB) (Edinger et al, 1998; Lauren et al, 2006; Pohlmann et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Figure 4 lists and plots the data which have been used here to measure the rate of SIV-induced cell death in such experiments. The results from these measurements are quite consistent across different experiments and publications (Forte et al 2003;Ilyinskii and Desrosiers 1996;Reitter and Desrosiers 1998). The death rate of SIV-infected PBMC in culture tends to be around a=0.3 days −1 (Figure 4) This corresponds to a half life of infected cells which is slightly greater than 2 days.…”
Section: Siv Dynamicssupporting
confidence: 76%
“…However, these experiments did not provide an estimate of the virus-induced death rate of infected cells, a, because the relative amounts of virus-induced and immune-mediated cell killing could not be distinguished in this study. However, it is possible to obtain a general idea about how fast SIV kills its cells from in vitro experiments in which SIV growth is monitored over time in PBMC (Forte et al 2003;Ilyinskii and Desrosiers 1996;Reitter and Desrosiers 1998). In such experiments, the virus first grows exponentially to a peak, and then declines exponentially (Figure 3b).…”
Section: Siv Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a number of studies revealed that various strains of SIV were able to infect and replicate in CCR5-null human PBMC as well as in CEMx174 cells, which lack CCR5 expression (62)(63)(64). These findings indicate that coreceptors other than CCR5 can support SIV entry and replication ex vivo.…”
Section: Discussionmentioning
confidence: 81%